Montagem audiovisual transmidiática: é possível pensar em relações entre imagens e sons de diferentes mídias? - Cheida, Samir Saraiva (2020)
This research aims to investigate the transmedia narrative strategies of the tv series “The Walking Dead” by Frank Darabont and Robert Kirkman. The tv series is an example of narrative complexity and its universe is distributed on television, in webisode, in comics, in online games, in video games, etc. As a hypothesis, the investigation uses editing theories to reflect on whether combinations of images and sounds from different media can build new meanings. The research seeks to identify how the editing can maintain the continuity between the different contents of “The Walking Dead” dispersed on multiplatforms and what new meanings can arise when all the images and sounds from the transmedia content of the series of “The Walking Dead” are juxtaposed. As a reference for analysis, we use the conceptions of the research line “Creation processes in Communication and Culture” led by Cecilia Almeida Salles. The concepts of montage and the role of the editor are highlighted as fundamental elements for the elaboration of the fictional universe and the aesthetics of the zombie series. Therefore, they are part of the complex network of creation of the transmedia system of "The Walking Dead". In addition, the dissertation will discuss concepts by authors that analyse television language, such as Henry Jenkins, Jason Mittel and Arlindo Machadoand to highlight how “The Walking Dead” was part of a new narrative model along with other tv series that emerged during the first decades of 2000. In this way, this research proposes an update of editing theories with the inclusion of transmedia storytelling as a driver of new relations between image and sound